Co-profiling of single-cell gene expression and chromatin landscapes in stickleback pituitary - Liang Liu; Jun Kitano; Shuji Shigenobu; Asano Ishikawa (Scientific Data)
Abstract The pituitary gland is a key endocrine gland with various physiological functions including metabolism, growth, and reproduction. It comprises several distinct cell populations that release multiple polypeptide hormones. Although the major endocrine cell types are conserved across taxa, the regulatory mechanisms of gene expression and chromatin organization in specific cell types remain poorly understood. Here, we performed simultaneous profiling of the transcriptome and chromatin landscapes in the pituitary cells of the three-spined stickleback (Gasterosteus aculeatus), which represents a good model for investigating the genetic mechanisms underlying adaptive evolution. We obtained pairwise gene expression and chromatin profiles for 5184 cells under short- and long-day conditions. Using three independent clustering analyses, we identified 16 distinct cell clusters and validated their consistency. These results advance our understanding of the regulatory dynamics in the pituitary gland and provide a reference for future research on comparative physiology and evolutionary biology.